2023
DOI: 10.1111/jog.15726
|View full text |Cite
|
Sign up to set email alerts
|

The significance of nonsurgical therapies for cervical infection of high‐risk human papilloma virus: A systematic review and meta‐analysis

Abstract: ObjectiveTo assess whether nonsurgical therapies were related with clearance of cervical infection of high‐risk human papilloma virus (hr‐HPV) or regression of mild abnormal cytology related with hr‐HPV.MethodsUntil March 2023, we identified a total of 10 424 women with cervical infection of hr‐HPV and 1966 women with mild abnormal cytology related with hr‐HPV from 44 studies that met the inclusion criteria.ResultsAfter systematically retrieving literature, we identified 2317 citations and 44 randomized contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 69 publications
(64 reference statements)
2
2
0
Order By: Relevance
“…A literature search identified meta-analysis studies evaluating the efficacy of non-surgical treatments on HPV. The results, similar to this study, indicated a significant effect on clearing HPV: Xiong et al 10 (p<0.00001), Huang et al 5 (p <0.0001), and Zhuang and Yang 11 (p<0.01). While these studies are up-to-date, providing a comprehensive assessment of non-surgical treatment methods, this study is crucial for focusing exclusively on the impact of herbal treatments and obtaining more specific data.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…A literature search identified meta-analysis studies evaluating the efficacy of non-surgical treatments on HPV. The results, similar to this study, indicated a significant effect on clearing HPV: Xiong et al 10 (p<0.00001), Huang et al 5 (p <0.0001), and Zhuang and Yang 11 (p<0.01). While these studies are up-to-date, providing a comprehensive assessment of non-surgical treatment methods, this study is crucial for focusing exclusively on the impact of herbal treatments and obtaining more specific data.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, herbal treatments were determined to be effective in clearing HPV infection (p=0.05). Although there is no meta-analysis specifically evaluating the effectiveness of herbal treatments in HPV treatment in the literature, a meta-analysis found a significant impact of biological and herbal studies on HPV clearance in a subgroup analysis similar to this study (p=0.01) 11 .…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations